2002
DOI: 10.1210/mend.16.3.0804
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Androgen Receptor (AR) Function by the Reproductive Orphan Nuclear Receptor DAX-1

Abstract: DAX-1 (NROB1) is an atypical member of the nuclear receptor family that is predominantly expressed in mammalian reproductive tissues. While a receptor function of DAX-1 remains enigmatic, previous work has indicated that DAX-1 inhibits the activity of the orphan receptor steroidogenic factor 1 and the estrogen receptors (ERs), presumably via direct occupation of the coactivator-binding surface and subsequent recruitment of additional corepressors. In vivo evidence points at a particular role of DAX-1 for the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(50 citation statements)
references
References 57 publications
1
46
0
1
Order By: Relevance
“…Although in vitro interactions between DAX-1 and AR have been reported (15), there have been no reports of interactions of endogenous DAX-1 and AR. Neither functional nor physical interactions between PR and DAX-1 have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although in vitro interactions between DAX-1 and AR have been reported (15), there have been no reports of interactions of endogenous DAX-1 and AR. Neither functional nor physical interactions between PR and DAX-1 have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Since the N terminus has 3 LXXLL-like motifs, it is possible that this is the interacting portion of DAX-1, although the C terminus is required for repression. Holter et al (15) found that the N terminus of DAX-1 was sufficient to cause aberrant localization of AR in the cytoplasm implicating this region in a physical interaction. In contrast, the N terminus of DAX-1 is sufficient to partially repress the activity of PR albeit to a lesser extent than the full-length (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations